The variability of particle backscattering coefficient in an oligo-to-hypertrophic cascading reservoir system: implications to TSM bio-optical model development - Alcantara, Enner [UNESP]; Watanabe, Fernanda [UNESP]; Bernardo, Nariane [UNESP]; Rodrigues, Thanan [UNESP] (Springer, 2016)
The particle backscattering coefficient (b(bp)) has been obtained either by equipment or semi-analytically based on relations between b(bp) and the remote sensing reflectance (R-rs). Correlation between b(bp) and R-rs can be significantly high allowing the development of bio-optical model to estimate the total suspended matter concentration [TSM] on water surface from satellite images. The development of such model to monitor cascading reservoir systems can be challenging since this type of water resources changes their biogeochemical composition from upstream to downstream; the water in such system can range from hypertrophic to oligotrophic state. The scientific question raised in this letter is that: in an oligo-tohypertrophic water system the models based on b(bp) will keep their good agreement or the influence of organic matter (e.g. chlorophyll-alpha) can affect this relationship? The aim of this letter was to analyze the b(bp) variability in a cascading reservoir system and search for empirical models that can capture the relationship between the b(bp) and [TSM]. The results showed that there are not only differences in the biogeochemical concentrations but also in the b(bp )from upstream to downstream. In addition there is an influence of chlorophyll-alpha concentration [Chl-alpha] on the relationship between b(bp) and [TSM] which prevents the bio-optical model development.
Keywords: Quasi-analytical algorithm; Case-2 waters; Particle backscattering; Trophic state